2021
DOI: 10.1111/ajt.16363
|View full text |Cite
|
Sign up to set email alerts
|

Estimating alloantibody levels in highly sensitized renal allograft candidates: Using serial dilutions to demonstrate a treatment effect in clinical trials

Abstract: Small reductions in calculated panel‐reactive antibody (cPRA) are associated with increased kidney transplantation in 100% cPRA patients. However, the high level of antibody in these patients is such that desensitization may reduce antibody but not cPRA, thus the cPRA change on undiluted serum with desensitization is an insensitive measure of effectiveness. We evaluated cPRA reduction, calculated per antibody titer, as a desensitization trial endpoint. To accomplish this, two serum samples from 20 kidney trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…We evaluated cPRA reduction per titer among 20 sensitized patients with a cPRA > 99.9% Figure 2 . We found that titer determination in a central laboratory using same lot reagents and batch testing leads to reproducible results and that the cPRA per dilution remains constant within approximately 1 titer if serum samples are obtained within 1 year ( 55 ). Transplant candidates with a cPRA of > 99.9% have vastly different quantities of antibody ( 55 ).…”
Section: Novel Approaches To Clinical Trial Design In Desensitizationmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated cPRA reduction per titer among 20 sensitized patients with a cPRA > 99.9% Figure 2 . We found that titer determination in a central laboratory using same lot reagents and batch testing leads to reproducible results and that the cPRA per dilution remains constant within approximately 1 titer if serum samples are obtained within 1 year ( 55 ). Transplant candidates with a cPRA of > 99.9% have vastly different quantities of antibody ( 55 ).…”
Section: Novel Approaches To Clinical Trial Design In Desensitizationmentioning
confidence: 99%
“…We found that titer determination in a central laboratory using same lot reagents and batch testing leads to reproducible results and that the cPRA per dilution remains constant within approximately 1 titer if serum samples are obtained within 1 year ( 55 ). Transplant candidates with a cPRA of > 99.9% have vastly different quantities of antibody ( 55 ). While the cPRA began to drop after only 1-2 dilutions for some candidates, other candidates remained at cPRA >99.9% even when their serum was diluted 1:4096.…”
Section: Novel Approaches To Clinical Trial Design In Desensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Percent cPRA has been the common metric to assess patients' sensitization, however, as we have recently shown, patients with cPRA >99.9% can still exhibit substantial heterogeneity with regards to the strength (amount) of their antibodies. 3 For example, two patients may have the exactly same cPRA but have antibodies of different titer (e.g., I:8 vs. >1:16:384). This additional "dimension" of sensitization is critical when attempting to compare results between different treatments, assuring we are not comparing apples to oranges (especially when desensitization is used in the context of deceased donor transplantation).…”
Section: Apples Oranges and Anything In Between: In Search Of The Bes...mentioning
confidence: 99%
“…This is a critical point as clinicians must remain thoughtful about when desensitization should be considered and how to personalize the approach. Percent cPRA has been the common metric to assess patients' sensitization, however, as we have recently shown, patients with cPRA >99.9% can still exhibit substantial heterogeneity with regards to the strength (amount) of their antibodies 3 . For example, two patients may have the exactly same cPRA but have antibodies of different titer (e.g., I:8 vs. >1:16:384).…”
mentioning
confidence: 99%